Animal‐to‐Human Dose Translation of Obiltoxaximab for Treatment of Inhalational Anthrax Under the US FDA Animal Rule. Issue 1 (7th December 2016) - Nagy, CF; Mondick, J; Serbina, N; Casey, LS; Carpenter, SE; French, J; Guttendorf, R
Abstract : Obiltoxaximab, a monoclonal antibody against protective antigen (PA), is approved for treatment of inhalational anthrax under the US Food and Drug Administration's (FDA) Animal Rule. The human dose was selected and justified by comparing observed obiltoxaximab exposures in healthy and infected New Zealand White rabbits and cynomolgus macaques to observed exposures in healthy humans, to simulated exposures in healthy and infected humans, and to serum PA levels in infected animals. In humans, at 16 mg/kg intravenous, obiltoxaximab AUC was >2 times that in animals, while maximum serum concentrations were comparable to those in animals and were maintained in excess of the concentration required for PA neutralization in infected animals for 2–3 weeks. Obiltoxaximab 16 mg/kg in humans provided exposure beyond that of 16 mg/kg in animals, ensuring a sufficient duration of PA neutralization to allow for adaptive immunity development. Our approach to dose translation may be applicable to other agents being developed under the Animal Rule.